Impact of MEK inhibition on T-cell infiltration and function after radiotherapy in KRAS-mutant lung cancer - Zheng, Yawen; Su, Chen; Pan, Jiachao; Wang, Yufeng; Zhao, Mengmeng; Zhang, Mingyan; Yan, Peng; Liu, Ning; Sun, Meili (Frontiers in Immunology, 2025)
IntroductionKi-ras2 (KRAS) mutation is a common driver of lung cancer, and KRAS-mutated tumors are relatively resistant to radiotherapy. Previously, we demonstrated that mitogen-activated protein kinase (MEK) inhibitors (MEKi) enhanced treatment efficacy by increasing the anti-tumor immune response after radiotherapy in KRAS-mutant tumors. In this study, we explored the potential mechanism underlying the MEKi-mediated increase in anti-tumor immune response.Methods and resultRNA sequencing revealed that the MEKi+radiotherapy combination significantly activated the chemokine signaling pathway. Blocking the C-X-C motif chemokine ligand 10 (CXCL10) receptor reduced T-cell infiltration in vivo. The MEKi+radiotherapy combination increased CXCL10 expression and activated the cyclic GMP–AMP synthase-stimulator of interferon genes (cGAS-STING) pathway in KRAS-mutant lung cell lines. Using a STING inhibitor and cGAS-knockout LLC cells, we showed that CXCL10 production was mediated by the cGAS-STING pathway via nuclear factor kappa B activation. This combination also increased DNA damage and apoptosis in KRAS-mutant lung cancer cell lines, triggering the cGAS-STING pathway. Western blot analysis revealed that MEKi reduced checkpoint kinase 2 phosphorylation after radiotherapy, hindering DNA repair and increasing DNA damage. Flow cytometry revealed that MEKi combined with radiotherapy boosted tumor-infiltrating CD4+ and CD8+ T cells in vivo, enhancing their cytotoxic and secretory functions. In an LLC-bearing mouse model, combining MEKi with varying radiotherapy doses and extending drug holidays revealed that low-dose radiotherapy with MEKi effectively controlled tumor growth.ConclusionOur findings suggest that MEKi activates the cGAS-STING-TANK-binding kinase 1-nuclear factor kappa B-CXCL10 axis post-radiotherapy in KRAS-mutant lung cancer, increasing T-cell infiltration and function, activating anti-tumor immunity, and inhibiting tumor growth. These results indicate the potential for clinical translation.